Żywioł przestrzeni czy ład pamięci? Przestrzeń jako źródło pamiętania i tożsamości społecznej — uwagi na temat procesu badawczego - Szczyrbowski, Jacek (Studia Etnologiczne i Antropologiczne, 2015)
Recent studies of the biographical identity of man go back to the concept of memory as the foundation of self-determination of an individual. Less attention is paid to social memory. Memory is rooted in a particular space. The more heterogeneous the space is (e.g. urban space), the greater diversity of memories it implies. Modern space becomes a manual for memory, focused on identifying, through space, locations in reminiscence. This article attempts to describe the role of space in the study of social memory. Emphasis is put on the research process, especially the interview which uses photographs and maps.